Politik Hukum Terhadap Qanun Nomor 6 Tahun 2014 Tentang Hukum Jinayah - Rahmiati, Rahmiati (SASI, 2020)
One of the provinces that get a portion of special autonomy is the province of Aceh. Privilege in Aceh include organizing the life of religion, culture, education, and the role of the clergy in the determination of regional policy. Laws enacted in Aceh is a law which is based on the teachings of Islam, namely: Syari teachings "at Islam which further implemented in Qanun. The people of Aceh in a fairly long history has made Islam as a way of life and part of the Acehnese people. One application of Islamic law in force in Aceh today is arranged in the form of Qanun. Qanun is the rule in the region, especially in Aceh, butbefore a Qanun will be set to qanuns official, would be a debate about whether or not Qanun is to be ratified. Feasibility will be tested politically through the involvement of community members to provide feedback, comments and suggestions for improvements to a bylaws. This process is called the politics of law.